2017
DOI: 10.1002/cbic.201700103
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl Photocleavage of Phosphopeptides Yields Truncated C‐Terminally Amidated Peptide Products

Abstract: The uranyl ion (UO2 2+) binds phosphopeptides with high affinity, and when irradiated with UV‐light, it can cleave the peptide backbone. In this study, high‐accuracy tandem mass spectrometry and enzymatic assays were used to characterise the photocleavage products resulting from the uranyl photocleavage reaction of a tetraphosphorylated β‐casein model peptide. We show that the primary photocleavage products of the uranyl‐catalysed reaction are C‐terminally amidated. This could be of great interest to the pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Uranium has an intermediate occurrence on earth, and so-called depleted 238 U is comparatively cheap as a hardly used byproduct when recycling spent nuclear fuel. Due to its slow decay with a half-life of several 10 9 years, it is only weakly radioactive (e.g., emitting less α radiation than natural uranium), but known in biology as one among the many chemically toxic heavy transition elements. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uranium has an intermediate occurrence on earth, and so-called depleted 238 U is comparatively cheap as a hardly used byproduct when recycling spent nuclear fuel. Due to its slow decay with a half-life of several 10 9 years, it is only weakly radioactive (e.g., emitting less α radiation than natural uranium), but known in biology as one among the many chemically toxic heavy transition elements. , …”
Section: Introductionmentioning
confidence: 99%
“…Photoexcitation is the most important method of activating the axial oxygen atoms of uranyl . (In this paper, electronic photoexcitation is designated by an asterisk *; a radicalic electron or hole by a dot • or circle ° , respectively; and, if necessary, physical adsorption on a carrier surface by a chemical formula.)…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the adsorption ability of BSA to uranyl showed that the protein exhibited a promising uranium adsorption ability of 5.67 mg g −1 within an adsorption time of 300 min in Tris‐HCl buffer (Figure 2a), which was used in the analysis of uranyl‐triggered protein photocleavage activity, [13d,e] and showed a high buffer capacity allowing to avoid the influence of environmental pH on the detection performance [16] . The UV/Vis adsorption spectrum of TPEs‐BSA exhibited peaks at 249 nm, 280 nm, and 340 nm (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Jørgensen and co-workers reported a procedure involving uranyl ion photocleavage of phosphopeptides to obtain the product of C-terminally amidation 23, 36 different from the previous work with free C termini 26. 37 The mass spectrum of uranyl photocleavage products of the peptide was consistent with the theoretical masses of products of C-terminally amidation 23, which strongly suggested that the formed peptides were C-terminally amidated, which was further verified by the results of collision induced dissociation (CID) experiments and control experiments with an exopeptidase.…”
Section: Scheme 14 Construction Of Phenol Derivativesmentioning
confidence: 99%